Strategy for Optimizing Vitamin B12 Production in Pseudomonas putida KT2440 Using Metabolic Modeling - Thomaz Satuye Prieto-de Lima; Keilor Rojas-Jimenez; Christopher Vaglio (Metabolites)
Background/Objectives: Vitamin B12 is very important for human health, as it is a cofactor for enzymatic activities and plays various roles in human physiology. It is highly valued in the pharmaceutical, food, and additive production industries. Some of the bacteria currently used for the vitamin production are difficult to modify with gene-editing tools and may have slow growth. We propose the use of the bacteria Pseudomonas putida KT2440 for the production of vitamin B12 because it has a robust chassis for genetic modifications. The present wok evaluates P. putida KT2440 as a host for vitamin B12 production and explore potential gene-editing optimization strategies. Methods: We curated and modified a genome-scale metabolic model of Pseudomonas putida KT2440 and evaluated different strategies to optimize vitamin B12 production using the knockin and OptGene algorithms from the COBRA Toolbox. Furthermore, we examined the presence of riboswitches as cis-regulatory elements and calculated theoretical biomass growth yields and vitamin B12 production using a flux balance analysis (FBA). Results: According to the flux balance analysis of P. putida KT2440 under culture conditions, the biomass production values could reach 1.802 gDW−1·h1·L−1, and vitamin B12 production could reach 0.359 µmol·gDW−1·h−1·L−1. The theoretical vitamin B12 synthesis rate calculated using P. putida KT2040 with two additional reactions was 14 times higher than that calculated using the control, Pseudomonas denitrificans, which has been used for the industrial production of this vitamin. Conclusions: We propose that, with the addition of aminopropanol linker genes and the modification of riboswitches, P. putida KT2440 may become a suitable host for the industrial production of vitamin B12.